Comparative study of brainstem evoked response audiometry in diabetic patients and non-diabetic subjects to assess the involvement of central auditory pathway - R., Shanthimalar; S., Muthuchitra; Nirmala S., Mary; Chandrika G., Udhaya; Rasith H., Mohamed (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Diabetes mellitus (DM) which is prevalent in world is associated with sensorineural hearing loss. Brainstem evoked response audiometry (BERA) is a simple, non-invasive procedure to detect early impairment of acoustic nerve and auditory pathway. The present study is under taken to evaluate the impact of DM on BERA parameters. Aim of the study was to compare the BERA of diabetic patients to those of age and gender matched controls to assess the involvement of central auditory pathway. Methods: A cross sectional study was conducted on 35 diabetic patients, aged 35 to 55 years, who were on treatment for at least 2 years, and 35 age and sex matched control participants, were subjected for BERA at 70,80 and 90 dB. The waveforms, absolute latency of wave I, wave III, wave V and interwave/ inter peak latency of I-III, III-V and I-V were analyzed with respect to both groups. Results: The absolute latency of wave III and wave V, interpeak/ interwave latency of I-III, interpeak/ interwave latency of I-V, III-V and absolute latency of wave V were highly significant at corresponding tested stimuli in the diabetic group compared to the control group. Conclusions: Early involvement of central auditory pathway in diabetic patients, can be detected with fair accuracy with auditory evoked potential studies; if done on a regular basis warrants meticulous glycemic control and prevents further damage.